Backyard pig feeding management practices in a lowland rice-based farming system - Gismundo, Wilfred D.; Gartner, Joseph A.; Suthad Setboonsarng; Sornthep Tumwasorn; Japan Government (Bangkok : Asian Institute of Technology, 1992)
Pig production in the Philippines is mainly small scale and backyard in operation mostly under the hands of small farmers . The sector accounts for 84 per cent of the total pig population in 1989. Feed and feeding management are considered major constraints limiting the growth and productivity of pigs in the country. This study aims to characterize the feeding management practices in a lowland rice-based farming system in the municipality of Tuao, Cagayan, Philippines. Its working hypothesis is that there is a low level of adoption on recommended pig feeding management practices by backyard raisers. Information was collected from farmers in two villages and grouped into three according to breed type raised. The types were native, upgrade and purebred. The level of adoption of eight recommended feedin g practices at different stages of life of pig in each breed type was determined using adoption scores of 1 to 3 with levels of low, medium and high assigned with increasing value of figure. The feeding practices are creep feeding, ad . libitum feeding, iron supplementation, vitamin-mineral supplementation, flushing, restricted energy feeding during gestation, increased feed one week before farrowing and feeding anti-constipation feed before farrowing. Gross margins and rates of return of 10 growing pigs were also calculated; each pig represent e d one farmer raiser. Feeding practices employed by raisers on native and upgrade pigs are from low to medium level and from medium to high level for purebred. Adoption of recommended feeding practices in piglet and growing pigs tend to increase with improved breed types. Adoption of recommended feeding practices for breeders is the same in all breed · types. A high level of adoption was observed for restricted feeding during gestation a nd feeding anti-constipation feed before farrowing for breeders. A medium level of adoption was found for creep feeding in piglets and for vitamin-mineral supplementation in all stages of life of the pig. Low level of adoption was recorded for ad libitum feeding, flushing, and increased feed before farrowing for breeders. Gross margins of growing pigs are positive but low based on rates of return to working capital and family labor. Rates of return for purebred are higher than upgrade and native. The advantage of high feed conversion efficiency of purebred growing pig was offset by the higher cost of commercially mixed feed provided to them relative to the cost of rice bran provided to native and upgrade pigs .
A thesis in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1992
Keywords: Swine -- Feeding and feeds; Agricultural systems